2004
DOI: 10.1007/s10267-003-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycelial growth of strains of the genera Suillus and Boletinus in media with a wide range of concentrations of carbon and nitrogen sources

Abstract: Suillus and Boletinus were studied using Ohta medium. In media with glucose or trehalose, all tested strains grew well. With mannose and cellobiose, strains generally grew well, except for one strain of Suillus. Utilization of dextrin and soluble starch differed with each strain, and that of sucrose and glycerol was low for all strains. Utilization of four amino acids, arginine, glutamic acid, aspartic acid, and alanine, was similar to that of ammonium tartrate for Suillus strains, but mycelial growth with ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
2
9
0
2
Order By: Relevance
“…This result was parallel with the suggestion of Hatakeyama and Ohmasa (2004) who found that the mycelial growth of Suillus and Boletinus was poor in sucrose contained medium. 1 Mycelial growth area and mycelial colony diameter were measured when it was completed in any of Petri plates at the end of the 11th day after mycelium inoculation for the current study; **Means followed by different letters in the same columns are statistically different according to Duncan's multiple range test (P<0.01).…”
Section: Resultssupporting
confidence: 90%
“…This result was parallel with the suggestion of Hatakeyama and Ohmasa (2004) who found that the mycelial growth of Suillus and Boletinus was poor in sucrose contained medium. 1 Mycelial growth area and mycelial colony diameter were measured when it was completed in any of Petri plates at the end of the 11th day after mycelium inoculation for the current study; **Means followed by different letters in the same columns are statistically different according to Duncan's multiple range test (P<0.01).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, only glucose and some other monosaccharides and disaccharides can be used for growth (Kusuda et al, 2007). It is possible that the low glucose level in the MMN medium (10 g·liter -1 ) was the reason the mycelium grew less, because, as reported by Hatakeyama and Ohmasa (2004a) El PDA fue el mejor medio de cultivo. Este resultado es conveniente para la selección y el aislamiento de las cepas pues es un medio fácil de preparar.…”
Section: Resultados Y Discusiónunclassified
“…El estudio del comportamiento y requerimientos de estos microorganismos en cultivo puro, constituye la base de la producción de inóculo; etapa necesaria para la micorrización controlada en plantas de interés forestal y posterior producción de esporomas (Díaz, Flores, & Honrubia, 2009a;Hatakeyama & Ohmasa, 2004a).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…(2) It is well known that adenosine is a precursor of cAMP, and the higher concentration improves the activity of cAMP-dependent protein kinase; however, the enzyme could suppress mycelial growth (Lubbehusen et al 2004). This effect was also found in other carbon and nitrogen components (Hatakeyama and Ohmasa 2004b). Kusuda et al (2007) reported catabolite suppression by higher concentrations of extra glucose in the ectomycorrhizal fungus Tricholoma matsutake.…”
mentioning
confidence: 82%